2015
DOI: 10.1007/s40263-015-0285-4
|View full text |Cite
|
Sign up to set email alerts
|

Practical Use of Newer Antiepileptic Drugs as Adjunctive Therapy in Focal Epilepsy

Abstract: This article lays the background for, and discusses the practical issues surrounding, the adjunctive use of the last four antiepileptic drugs (AEDs) to be licensed for the treatment of pharmacoresistant focal seizures in the UK and elsewhere. More than 30% of adolescent and adult patients will not be fully controlled on the currently available therapeutic armamentarium. After not responding to their first three AED schedules, only a handful of patients attained seizure freedom on subsequent regimens. To optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 81 publications
0
9
0
2
Order By: Relevance
“…Anti-epileptic treatment centres on the greatest reduction of the number of epileptic seizures, while minimising adverse effects and long-term toxicity as far as possible. Clinical evidence shows that monotherapy with anti-epileptic drugs (AEDs) is effective in 70% of patients [5]. The remaining 30% need adjunctive treatment to control the seizures [6] and, of these, approximately 25% have epilepsy that is difficult to control, refractory or resistant to AEDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-epileptic treatment centres on the greatest reduction of the number of epileptic seizures, while minimising adverse effects and long-term toxicity as far as possible. Clinical evidence shows that monotherapy with anti-epileptic drugs (AEDs) is effective in 70% of patients [5]. The remaining 30% need adjunctive treatment to control the seizures [6] and, of these, approximately 25% have epilepsy that is difficult to control, refractory or resistant to AEDs.…”
Section: Introductionmentioning
confidence: 99%
“…The neurologist has more than 20 AEDs available for the treatment of epilepsy, some of which have numerous side effects and interactions that can complicate patient treatment and management, especially for those with refractory epilepsy [5]. Since 1993, more than 12 new AEDs have been approved that have an effect on seizure control and a better tolerability profile, as well as a lower risk of drug interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Although most drugs provide seizure control in polytherapy, treatment is discontinued because it is not tolerated due to drug-drug interactions, toxicity, systemic adverse effects, even if it is effective. In the literature, the success of treatment with monotherapy in the refractory epilepsy group was 49.5%, seizure-free status was achieved in 13.3% of patients in the second add-on treatment, and this success decreased to 3.3% with the addition of a third antiepileptic drug (9). In the refractory epilepsy group, it was observed that the success rate was low with add-on treatment in patient groups in which seizure control was not achieved with the first drug (4,9).…”
Section: Discussionmentioning
confidence: 99%
“…У 1 пациента на фоне приема ПЕР были зафиксированы суицидальные мысли [29]. По данным ретроспективного анализа психических и поведенческих побочных эффектов, на фоне приема ПЕР нередко отмечались гнев, агрессия и враждебное поведение, особенно при приеме высоких доз препарата [30][31][32], в основном это касалось подростков [32].…”
Section: побочные эффектыunclassified
“…Так как доза 4 мг/сут одновременно является начальной эффективной, обычно рекомендуют относительно быстрый подъем дозы ПЕР до 4 мг/сут, после чего дальнейшая титрация проводится более осторожно. В случае же развития побочных эффектов при наличии хорошей эффективности возможно разделить дозу на два приема [30]. Что касается раздражительности и агрессии, описанных на фоне приема ПЕР, то, в отличие от таковых на фоне приема леветирацетама, данные нежелательные явления обычно развиваются в самом начале приема ПЕР, а не с увеличением его дозы, хотя также являются дозозависимыми.…”
Section: практические рекомендацииunclassified